2018
DOI: 10.3920/bm2017.0103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacillus subtilis C-3102 on loose stools in healthy volunteers

Abstract: Ingestion of Bacillus subtilis C-3102 spores (C-3102) has relieved the symptoms of diarrhoea in piglets and changed the composition of gut microbiota in humans. Recently, it was suggested that the composition of the human gut microbiota affects stool consistency. In this study, a double-blind, randomised, placebo-controlled trial was conducted to assess the preventive effects of chronic diarrhoea in healthy volunteers with loose stools by ingestion of C-3102. The results showed that oral doses of C-3102 tablet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…Analysis of the composition of the in vitro human colonic microbiota model by next generation sequencing. Microbiota composition was determined with a MiSeq V2 kit (Illumina, San Diego, CA, USA), as described previously 15 .…”
Section: Growth Activity Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the composition of the in vitro human colonic microbiota model by next generation sequencing. Microbiota composition was determined with a MiSeq V2 kit (Illumina, San Diego, CA, USA), as described previously 15 .…”
Section: Growth Activity Ofmentioning
confidence: 99%
“…In addition, ingestion of C-3102 at 8.0 × 10 8 colony forming units (cfu)/day for 8 days in human subjects increased the relative abundance of the genus Bifidobacterium and decreased the number of Enterobacteriaceae 14 . Recently, it has been reported that ingestion of C-3102 at 2.2 × 10 9 cfu/day for 8 weeks improved loose stool symptoms in adults 15 , and ingesting 3.4 × 10 9 cfu/day for 24 weeks increased the abundance of Bifidobacterium in postmenopausal women 16 . Therefore, C-3102 has the potential to modulate the gut microbiota to improve fecal properties in humans.…”
mentioning
confidence: 99%
“…Based on prior testing of probiotic B. subtilis, no safety concerns were expected even at high doses [26][27][28][29][30][31][32]. Therefore, dosage levels for the study were chosen based on the intended dose for the final product, namely 10 9 CFU.…”
Section: Methodsmentioning
confidence: 99%
“…Fecal samples were collected at 0 and 12 weeks, and fecal DNA was extracted by the bead beating method as previously described [34]. Amplification of the 16S rRNA sequence was performed with the primer set of Tru357F (5 -CGCTCTTCCGATCTCTG TACGGRAGGCAGCAG-3 ) and Tru806R (5 -CGCTCTTCCGATCTGACGGACTACHVGGGTWTCTAAT-3 ) as described previously [35].…”
Section: Analysis Of Fecal Microbiotamentioning
confidence: 99%